Peran PKn Dalam Membentuk Kompetensi Demokrasi Digital Pada Siswa Sekolah Dasar di Era Digital: Sebuah Model Konseptual Terintegrasi - Ni Luh Made Ari Krisna Yanti; Dewa Bagus Sanjaya; I Nengah Suastika (Jayapangus Press, 2026)
The development of digital technology has transformed social interaction patterns and character formation among elementary school students, posing serious challenges to instilling democratic values such as tolerance, communication ethics, and social responsibility. This study aims to analyze the role of Civic Education (PKn) in fostering a democratic spirit, identify implementation challenges, and develop a conceptual model as the research novelty. This research employed a qualitative descriptive method through systematic literature review and in-depth interviews with teachers at SD Negeri 2 Tabanan. The findings reveal that the main challenges lie not only in students' digital literacy but also in the gap in teachers' digital competence, the absence of evaluation instruments for democratic behavior in digital spaces, and the weak school-family-community tripartite collaboration. The novelty of this research is the Integrated Conceptual Model (ICM) , which connects four main components: digital democracy pedagogy, digital literacy for teachers and students, tripartite collaboration, and digital behavior evaluation instruments. This model serves as the article's original contribution to holistically integrating democratic education, character education, and digital literacy at the elementary school level. In conclusion, the successful formation of a democratic spirit in the digital era can only be achieved through the implementation of the ICM that combines participatory learning, critical use of technology, and digital behavior-based evaluation.